Effect of student activity participation on accounting education - Yeon-Hee Park; Tae-Young Paik; Jeong-Ho Koo (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Accounting education focuses on delivering knowledge to students. Most student are passive, behaving as bystanders or listeners in lecturer-oriented learning. However, student-centered learning requires active and positive engagement from students to generate effective learning. Board games represent a key driving tool in inducing student participation and interest in active learning. This study investigates whether the active participation of students in class activities has positive effects on accounting education. Specifically, it tests whether active student involvement in board game activities in introductory accounting courses contributes to effective learning. There were a few key findings. Firstly, the more actively that students participate in the game, the higher their favorable changes are in terms of perception of accounting. Secondly, the higher their positive perceptions are, the higher the effects of accounting education are. These results imply that the active involvement of learners is a precondition for the effect of accounting education activities, and that positive perception is a mediator for learning effects.
Keywords: 650; accounting education; active learning; board game; learning effects; team activities